Inhibition of cellular RNA methyltransferase abrogates influenza virus capping and replication - Tsukamoto, Yuta; Hiono, Takahiro; Yamada, Shintaro; Matsuno, Keita; Faist, Aileen; Claff, Tobias; Hou, Jianyu; Namasivayam, Vigneshwaran; vom Hemdt, Anja; Sugimoto, Satoko; Ng, Jin Ying; Christensen, Maria H.; et al. (Science (American Association for the Advancement of Science), 2023)
Orthomyxo- and bunyaviruses steal the 5′ cap portion of host RNAs to prime their own transcription in a process called “cap snatching.” We report that RNA modification of the cap portion by host 2′-O-ribose methyltransferase 1 (MTr1) is essential for the initiation of influenza A and B virus replication, but not for other cap-snatching viruses. We identified with in silico compound screening and functional analysis a derivative of a natural product from Streptomyces , called trifluoromethyl-tubercidin (TFMT), that inhibits MTr1 through interaction at its S -adenosyl- l -methionine binding pocket to restrict influenza virus replication. Mechanistically, TFMT impairs the association of host cap RNAs with the viral polymerase basic protein 2 subunit in human lung explants and in vivo in mice. TFMT acts synergistically with approved anti-influenza drugs. Some virus families hijack part of their hosts’ RNA to enable their own replication in a process called cap snatching. Before they can enact a snatch, influenza viruses specifically require host cap maturation by a host methyltransferase called MTr1. Tsukamoto et al . screened a compound library and found that trifluoromethyl-tubercidin (TFMT) inhibits host Mtr1 and suppresses virus replication. TFMT inhibits host cap RNA maturation and impedes binding of host cap RNAs with the viral polymerase, thus disabling viral replication. TFMT was not only effective in inhibiting viral replication in human lung cells, but was also effective in mice, displayed little toxicity, and acted in synergy with approved anti-influenza drugs. —CA Inhibition of a host methyltransferase interferes with binding of host cap RNAs to viral polymerase and inhibits influenza virus replication.